2017
DOI: 10.1128/aem.01231-17
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin-Producing Serogroup O91 Escherichia coli Strains Isolated from Food and Environmental Samples

Abstract: Shiga toxin-producing Escherichia coli (STEC) strains of the O91:H21 serotype have caused severe infections, including hemolytic-uremic syndrome. Strains of the O91 serogroup have been isolated from food, animals, and the environment worldwide but are not well characterized. We used a microarray and other molecular assays to examine 49 serogroup O91 strains (environmental, food, and clinical strains) for their virulence potential and phylogenetic relationships. Most of the isolates were identified to be strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Genetic and phylogenetic analyses of STEC strains propose that some strains isolated from bovines and food have the potential to cause severe illness (Feng et al, 2017;Feng et al, 2014;KrĂźger et al, 2015). In agreement with these observations, previous studies in our laboratory suggest that Stx phages from some bovine strains are able to be induced to similar levels than those from clinical isolates (KrĂźger et al, 2011;Lenzi et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Genetic and phylogenetic analyses of STEC strains propose that some strains isolated from bovines and food have the potential to cause severe illness (Feng et al, 2017;Feng et al, 2014;KrĂźger et al, 2015). In agreement with these observations, previous studies in our laboratory suggest that Stx phages from some bovine strains are able to be induced to similar levels than those from clinical isolates (KrĂźger et al, 2011;Lenzi et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…E. coli and Salmonella were recovered from 37.2% and 20.2% of all tested birds, respectively. Serotyping of the isolated E. coli revealed the wide prevalence of certain E. coli serotypes, which are more frequently associated with avian Collibacillosis such as O1 and O78 [32], and Shiga Toxin-Producing serotypes such as O121, O91, and O26 [33,34] were also recovered. Potentially, a higher prevalence of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, O91 strains have been regularly isolated from patient samples and could be found in different foods [ 7 , 27 , 49 , 51 , 52 ]. Recent studies showed that O91 isolates of various origin (food, environment, and humans) share similar genotypic profiles, are phylogenetically related, could be mainly attributed to cattle as a reservoir for human infections, and, thus, could potentially lead to severe human infections [ 53 , 54 ]. Comparing the infection numbers and distribution in detected serotypes of 2016 to the three previous years, there is an increase in the number of cases, but the overall distribution of LEE-positive and LEE-negative pathogens remained steady throughout those years [ 46 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%